2013
DOI: 10.1596/1813-9450-6352
|View full text |Cite
|
Sign up to set email alerts
|

Government Connections and Financial Constraints: Evidence from a Large Representative Sample of Chinese Firms

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…In SOEs, the inherent connection with government through the government ownership enables SOEs to receive various supports from the state (Cull et al, 2015;Chen et al, 2017). In SOEs, we expected that political connections distort M&A decisions, and result in worse M&A performance.…”
Section: Introductionmentioning
confidence: 99%
“…In SOEs, the inherent connection with government through the government ownership enables SOEs to receive various supports from the state (Cull et al, 2015;Chen et al, 2017). In SOEs, we expected that political connections distort M&A decisions, and result in worse M&A performance.…”
Section: Introductionmentioning
confidence: 99%
“…In China, politically connected firms borrow from state‐controlled banks easily (Li et al, ). Consequently, failure to forge ties with officials reduces firms’ chances of survival in China by limiting their investment opportunities (Xu et al, ) and making external financing inaccessible (Cull et al, ; Li et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, social exchange theory (SET) is based on the direct reciprocity mechanism, in which person A becomes obligated to repay person B for past support. Many studies of political affiliations follow the traditional lens of SET (e.g., Cull et al, ; Xu et al, ; Xu et al, ) and generally assume that CEOs have direct access to political officials in the first place. However, they fail to distinguish presumed access from actual access (e.g., official visits).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Cull et al (2015) demonstrated that political connections can reduce financial constraints and make it easier to acquire financing from state-owned banks. For example, Cull et al (2015) demonstrated that political connections can reduce financial constraints and make it easier to acquire financing from state-owned banks.…”
Section: Literature Review Of Political Connectionsmentioning
confidence: 99%
“…Existing empirical studies find mixed evidence regarding the role of the firm's political connections, with some of the literature (Cull, Li, Sun, & Xu, 2015;Feng et al, 2015) supporting the notion that they generate higher value for firms, because of the easier access to capital, the lower cost of financing, and preferential tax treatment. First, instead of considering a firm's political connections, which are prone to the aforementioned potential "double-edged sword" problem, we examine an external source of political connection, namely, the decision to appoint a politically connected financial advisor.…”
Section: Introductionmentioning
confidence: 99%